Pelatihan Pembuatan Gantungan Pot Berbasis Tali Katun Makrame dan Tali Kain melalui Pendekatan Community Development Practice - Adhan (LPPM STIE Mujahidin, 2026)
This community service activity aimed to improve the creativity and skills of parents of students at Satuan PAUD Sejenis (SPS) through training in making flower pot hangers using macramé cotton rope and fabric rope. The activity was carried out using the Community Development Practice approach combined with the Peer Assisted Learning (PAL) method through participatory training, demonstrations, direct practice, and mentoring by student assistants. The training materials included the introduction of tools and materials, the use of 3-strand and 4-strand macramé cotton rope as well as 3-strand fabric rope, and the practice of basic macramé knot techniques such as the lark’s head knot and square knot in making flower pot hangers. The results of the activity showed that the participants were able to understand the basic knotting techniques and independently produce flower pot hanger crafts. Based on the evaluation results, approximately 95% of participants successfully made flower pot hangers using macramé cotton rope and fabric rope properly. The implementation of the Peer Assisted Learning (PAL) method helped accelerate the transfer of knowledge and skills to participants through direct mentoring during the practice sessions. In addition to improving participants’ creativity and skills, this activity also increased awareness of the potential development of handicrafts as a household creative economy business opportunity.